The expression of miR-17 and miR-29a in placenta-derived exosomes in LPS-induced abortion mice model: An experimental study - Tahereh Jalilvand; Reza Salarinia; Hasan Namdar Ahmadabad; Mohammadreza Safdari (Shahid Sadoughi University of Medical Sciences, 2021)
Background: The expression pattern of microRNAs in placenta-derived exosomes plays a crucial role in the regulation of immune responses and inflammation at the fetal-maternal interface. Objective: Considering the immunomodulatory properties of miR-17 and miR-29a, we determined their expression levels in placenta-derived exosomes in a lipopolysaccharide (LPS)-induced abortion mice model. Materials and Methods: A total of 14 pregnant BALB/c mice, aged 6-8 wk, were randomly divided into two groups (n = 7/each) on the gestational day 11.5. While the mice in the experimental group were treated with LPS, those in the control group were treated with Phosphate buffered saline; 5 hr after the treatment, the placental cells were isolated and cultured for 48 hr. Then, the cell culture supernatants were collected and used for isolation of exosomes. The isolated exosomes were confirmed by western blot and scanning electron microscopy. The miRNAs were then extracted from exosomes, and cDNA synthesized. The expression levels of miR-17 and miR-29a were evaluated by quantitative real-time PCR analysis. Results: Our results showed that the expression levels of miR-29a in placenta-derived exosomes obtained from the experimental group increased significantly compared to the control group. Also, the expression levels of miR-17 in the placenta-derived exosomes obtained from the experimental group were found to decrease; however, it did not show significant changes compared with the control group (p > 0.05). Conclusion: Inflammatory reactions at the fetal-maternal interface can alter miRNAs expression patterns in placenta-derived exosomes, especially miRNAs with immunomodulatory effects such as miR-29a.